Komitmen Kepala Sekolah dalam Peningkatan Layanan Pendidikan - Beni Chandra Purba (PT. Penerbit Tiga Mutiara, 2023)
This study aims to describe the implementation of educational services by school principals and to analyze the level of their leadership commitment in supporting the continuous improvement of education quality. As central figures in the governance of educational institutions, school principals play a multidimensional role, encompassing strategic, managerial, pedagogical, and symbolic functions that simultaneously influence the effectiveness of the school organization. The findings indicate that the principal’s level of commitment is positively correlated with the quality of strategic planning, resource management, and the development of a collaborative work culture oriented toward achieving institutional goals. Principals who demonstrate a high level of dedication to enhancing education quality tend to be more effective in building constructive supervision systems, establishing transformative visions and missions, and mobilizing stakeholder participation in data-driven decision-making processes. This study also affirms that the successful implementation of educational service programs is highly dependent on the principal’s capacity to navigate policy dynamics, resource limitations, and the socio-cultural complexities of the school environment. From a theoretical standpoint, this study reflects the relevance of transformational leadership and evidence-based management approaches as foundational to building adaptive and accountable educational institutions. The implications of this research emphasize that enhancing the professional capacity of school principals (in terms of integrity, managerial competence, and strategic vision) is a key determinant in realizing holistic, relevant, and sustainable educational service quality.